Pengolahan Statistik Asuhan Kesehatan Dalam Pengolahan Data Di Semen Padang Hospital - Rahmanisa Dwi Putri (Iris Journal of Health Information Management, 2022)
Statistics are needed as a basis for decision making in every area of life, one of which is hospitals. Hospital statistics are statistics that use and process hospital service data sources to produce information, facts and knowledge related to hospital services. Results of data processing sourced from secondary data on inpatients at Semen Padang Hospital (SPH) for the period April 2019, patient data was 922, number of beds was 144 units. Data processing was carried out using Microsoft Excel and presented in the form of Barber Johnson tables and graphs. The results obtained were BOR 60%. BTR 0 times. TI 2 days and ALOS 3 days. Based on the results obtained, BOR and TI are at the efficient point, while BTR and ALOS are not at the efficient point. In table RL4a, the age group 45-64 years is 297 patients. The gender grouping was 449 patients male and 472 female patients, according to disposition, 907 patients were alive and 14 patients died. From the main diagnosis grouping based on ICD-10 code A01.0, 55 patients were diagnosed with Thypoid Fever. The frequency of the main diagnosis based on BAB in ICD-10 is CHAPTER I (Certain infectious and parasitic disease) at 14.66% or 135 patients. The procedure grouping based on ICD-9 is SC (Caesarean Section) with procedure code 77.99 for 34 patients. Based on the DTD code with code 002 Thypoid Fever there were 55 patients.